The effect of air pollutants on COPD-hospitalized patients in Lanzhou, China (2015–2019) - Jin, Limei; Fang, Shuya; Nan, Yaxing; Hu, Jihong; Jin, Hua (Frontiers in Public Health, 2024)
Background: Lanzhou is the largest heavy industrial city in northwest China and it is a typical geographical valley-like-city, while there are few studies on the relationship between air pollutants and COPD, and their respective sample sizes are small, which leads to inconsistent results. The aim of this study is to analyze the effects of air pollutants on COPD hospitalizations in Lanzhou, China.Methods: An ecological time-series study with distributed lag non-linear model (DLNM) was used for analysis.